Epidemiological study of maternal risk factors influencing the incidence of preterm birth in developing countries - Tondong, Henrietta Imelda; Tempali, Sri Restu; Kusika, Sri yanti; Pani, Widya (Institute of Computer Science (IOCS), 2025)
Preterm birth (PTB) remains a significant public health challenge in developing countries, contributing to high neonatal morbidity and mortality rates. This qualitative literature review aims to explore the maternal risk factors influencing the incidence of preterm birth in these regions. By examining existing studies, the review identifies key maternal characteristics such as age, nutritional status, socioeconomic factors, reproductive history, and healthcare access, which contribute to the risk of PTB. Additionally, the review highlights the role of environmental factors, including stress, pollution, and infections, in increasing preterm birth rates. The findings suggest that improving maternal healthcare, enhancing public awareness, and addressing socioeconomic disparities are essential in reducing the prevalence of preterm birth in developing countries. This study provides a comprehensive understanding of the factors influencing PTB and offers insights for developing targeted interventions aimed at reducing its incidence in resource-limited settings.